1993
DOI: 10.1111/j.1440-1673.1993.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker function during irradiation: in vivo and in vitro effect

Abstract: With an ageing population in Australia, one would expect the probability of treating cancer patients who have a cardiac pacemaker to increase. In this paper the effect of ionizing radiation and electromagnetic interference on pacemaker function is discussed. A case of a cancer patient, with pacemaker, treated with radiotherapy without ill effect, is described. Concurrently, four pacemakers were tested in vitro with gamma radiation from a 60 Cobalt machine and no adverse effect was found. A list of precautions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The effect of ionizing radiation on pacemaker and ICD has been extensively analyzed in the literature by in vitro studies 6,8,10,[16][17][18][19][20][21][22][23][24][25]31 . A large number of studies has covered the more modern types of pacemakers 6,17,18,32,33 , but study groups are small, in vitro and only some types of stimulators are included.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of ionizing radiation on pacemaker and ICD has been extensively analyzed in the literature by in vitro studies 6,8,10,[16][17][18][19][20][21][22][23][24][25]31 . A large number of studies has covered the more modern types of pacemakers 6,17,18,32,33 , but study groups are small, in vitro and only some types of stimulators are included.…”
Section: Discussionmentioning
confidence: 99%
“…The few data available in vivo are mainly on case reports. There are no uniform recommendations from the manufacturers, and these data are of difficult availability (Table 1) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with observational findings report the occurrence of EMI during radiation therapy, [31][32][33] whereas other observational studies and case reports indicate no apparent EMI effects (Category B2-B3 evidence). 34,35 Studies with observational findings report the occurrence of EMI during lithotripsy, 36,37 whereas other observational studies and case reports indicate no apparent EMI effects (Category B2-B3 evidence). 38 -41 No studies were found that reported EMI during electroconvulsive therapy (ECT) (Category D evidence).…”
Section: Preoperative Preparationmentioning
confidence: 99%
“…Radiation therapy is known to have an effect on pacemaker and implantable cardioverter-defibrillator function [ 6 ] via electromagnetic interference or through the effects of ionizing radiation [ 7 11 ]. The effects of radiation therapy on pacemakers has been studied in detail in the past [ 11 16 ]. Based on the studies’ results, the American Association of Physicists in Medicine (AAPM) presented recommendations for irradiation of pacemaker patients in 1994 [ 7 ] and divided the hazards into two categories—electromagnetic noise interference and radiation damage.…”
Section: Introductionmentioning
confidence: 99%